Synthesis and characterization of Ag-ZnO using citrus reticulata peel extract - Joan Jepngetich; Peter W Njoroge; Sylvia Opiyo; Sharon Kiprotich (Materials Research Express)
To minimize the use of fossils fuels, solar cells have been considered to be effective despite facing major setbacks such as its cost and effectiveness. In this research Ag-ZnO was synthesized using Citrus reticulata as capping agents to be used as photoanoade in solar cell so that it can improve effectiveness of solar cell. Pure and Ag-ZnO were synthesized using chemical precipitation method with Citrus reticulata peel extract as a capping agent. The effects of capping agent on material properties of ZnO and Ag-ZnO were reported. The results obtained showed that capping agents had major effects on the properties of nanoparticles. Several techniques were used to characterize the as-prepared and annealed ZnO and Ag-ZnO nanoparticles. X-ray diffraction was used to determine the crystal structure. The results obtained showed that both capped and uncapped ZnO and Ag-ZnO maintained the hexagonal wurtzite structure. This showed that the dopant occupied the interstitial site of the precursor materials. Derby Scherrer formula was used to calculate the crystal size, the results obtained showed that capping agents reduced the crystal size of nanoparticles. All nanoparticles formed were in the range of 8–14 nm. Fourier transform infrared spectroscopy showed the stretching vibration of Zn-O between 470–420 cm ^−1 wavenumbers. Photoluminescence spectroscopy (PL) and Ultra violet visible spectroscopy (UV–vis) were used to study the optical properties of nanoparticles. PL showed significant shift towards the near band edge region when nanoparticles were doped. In the UV–vis the Tauc’s equation was plotted and used to determine the bandgap energies of nanoparticles. Uncapped ZnO had a bandgap of 3.34 and the capped ZnO had a bandgap of 3.52 eV. When doped the bandgap energies increased to 3.85 and 3.68 for pure and capped Ag-ZnO nanoparticles. Scanning electron microscopy was used to determine the morphological properties of nanoparticles, the results obtained showed that capping agents stabilizes and improve the crystal structure of nanoparticles. Capped ZnO had the best morphological properties.